Protective effects of tomato powder on lipid peroxidation and antioxidant status in PUFA-enriched diets in quail - Şahin, Kazım; Orhan, Cemal; Hayirli, Armagan; Tuzcu, Mehmet; Tokmak, Muhammed; Şahin, Nurhan (Elsevier, 2026)
Enriching poultry meat with polyunsaturated fatty acids (PUFA) is a common strategy to enhance its nutritional value; however, this practice increases the risk of lipid peroxidation, potentially compromising meat quality. This study evaluated the effects of tomato powder (TP) supplementation on antioxidant status, muscle fatty acid composition, and lipid peroxidation in quails fed PUFA-enriched diets. A total of 180 quails were assigned to six dietary treatments in a 2 x 3 factorial arrangement with two PUFA levels (15 or 45 g/100 g fat) and three TP levels (0%, 2.5%, or 5%) for 42 days. Each treatment was replicated across 10 cages, with three birds per cage. Statistical analyses were conducted using the MIXED procedure in a randomized design. Data are presented as LS mean +/- SEM. Given the multifactorial design and limited sample size, results were interpreted as significant (P <= 0.05) or as a trend (0.05 < P <= 0.10). Cumulative feed intake, body weight gain, and feed conversion ratio were not significantly affected. High-PUFA diets reduced serum and muscle lycopene concentrations by 42.9% (p = 0.0002) and 24.7% (p = 0.0124), and decreased muscle alpha-tocopherol by 41.1% (p < 0.0001). Simultaneously, serum and muscle malondialdehyde (MDA) levels increased by 27.6% (p = 0.0129) and 55.2% (p < 0.0001). TP supplementation enhanced serum (p < 0.0001) and muscle lycopene concentrations (p < 0.0001), as well as muscle retinol levels (p = 0.0026), while markedly reducing MDA concentrations in both serum (p = 0.0043) and muscle (p < 0.0001). Significant interactions between PUFA and TP were detected for serum lycopene (p < 0.0137), with trends also observed for serum MDA (p = 0.1622) and muscle MDA (p = 0.0944). As expected, high-PUFA diets altered the muscle fatty acid profile by reducing total saturated fatty acids (26.6% vs. 33.1%; p < 0.0001) and increasing total PUFA (37.0% vs. 13.2%; p < 0.0001) and omega-3 fatty acids (21.5% vs. 2.0%; p < 0.0001). In conclusion, TP supplementation alleviates PUFA-induced oxidative stress by enhancing lycopene deposition in muscle, thereby improving antioxidant capacity and reducing lipid peroxidation in PUFA-enriched meat products.
Keywords: Tomato powder; Polyunsaturated fatty acids; Lipid peroxidation; Antioxidant status